Effect of e-Government on Improving the Quality of Public Services in Serang Municipality - Sri Wahyuningsih; Rachmi Yulianti; Rethorika Berthanilla (Sawala : Jurnal Administrasi Negara, 2021)
This study aims to find out "How is the implementation of E-Government RABEG (Reaction to Citizen News) applications in Serang City and whether the implementation of E-Government through RABEG applications can improve the quality of public services in Serang City?". This study uses quantitative methods with statistical analysis using SPSS software. The data used are primary and secondary data, primary data obtained by conducting interviews and distributing questionnaires to 83 respondents who have been determined and are considered representative to answer the research questionnaire. Meanwhile, secondary data were obtained from literature review and documentation of data related to research. Statistical analysis in this study includes data validity test, data reliability test, data normality test, simple linear regression analysis, determinant coefficient, and correlation coefficient. The results of research and statistical analysis show that the implementation of the E-Government system for the RABEG application in Serang City is quite good, and the results of testing the research hypothesis indicate that there is a significant positive effect between E-Government on improving the quality of public services in Serang City.